Anatomical and visual outcome of intravitreal bevacizumab (Avastin) in patients with diabetic macular edema - Vyas, Shyam; Thapa, Raba; Bajimaya, Sanyam; Pradhan, Eli; Paudyal, Govinda (Nepalese Journal of Ophthalmology, 2016)
Background: Intravitreal bevacizumab has been shown to be an effective treatment of diabetic macular edema. Objective: To assess the anatomical and visual outcome of intravitrealbevacizumab (Avastin) in patients of diabetic macular edema. Materials and methods: 52 eyes of 33 patients with diabetic retinopathy with CSME were included in this study. Detailed ophthalmic examination, including best-corrected visual acuity(BCVA), stereoscopic biomicroscopy, and retinal thickness measurement by Optical coherence tomography (OCT), was done at baseline and at each follow- up visit. All patients were treated with 0.05 mL intravitreal injection containing 1.25 mg of bevacizumab and repeat injection was given in cases of recurrent/persistent subretinal or intraretinal fluid shown by OCT and deterioration of BCVA. Results: All patients completed 6 months of follow-up with mean number of 2.78 intravitreal injections per eye.The mean BCVA at baseline was 0.80 log MAR, with significant changes 0.68 (p=0.012), 0.63 (p=